PENGARUH MODEL PEMBELAJARAN TEAM GAMES TOURNAMENT TERHADAP HASIL BELAJAR SISWA PEMBELAJARAN TEMATIK TEMA 4 SUBTEMA PEKERJAAN SEKITARKU SISWA KELAS IV SEKOLAH DASAR - Fatmawati M Yusuf; Regina Fredika Sipayung (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2024)
The purpose of this study was to evaluate the impact of the use of the Team games tournament learning model on student learning outcomes on theme 4 subtheme of Work Around grade IV SD. This study uses quantitative methods with Pre-Experimental Design design, applying One Group Pretest-Posttest research design with class V SD Gracia Sustain selected as a sample of 30 students and sampling using saturated sampling technique, where the entire population is sampled.The results of data analysis and hypothesis testing show that the application of the Team games tournament learning model has a significant impact on student learning achievement. The significance value (2-tailed) obtained is smaller than 0.05 (0.00 <0.05), and the tcount value is greater than the ttable (13.152 > 2.048). Therefore, the H0 hypothesis is rejected and the Ha hypothesis is accepted, so it is concluded that the use of the Team games tournament learning model has a positive impact on the learning outcomes of grade IV students on the subtheme Jobs Around Me grade IV Elementary School.